Estimation of external walls decisions of multistorey residential buildings applying methods of multicriteria analysis - Zavadskas, Edmundas Kazimieras; Ustinovičius, Leonas; Turskis, Zenonas; Ambrasas, Gintautas; Kutut, Vladislavas (Technological and Economic Development of Economy, 2005)
This paper analyses the most widespread designs of external walls of the multi‐storey residential buildings now in use. Such 49 alternative designs of external walls of multi‐storey residential buildings are analyzed using multicriteria analysis program under uncertainty. Few ways of the decision are applied for the decision of the problem: the method of distance to an ideal point, Baye’s rule and Wald’s rule. To project and understand effective construction of a building, it is necessary to execute exhaustive analysis of all decisions (planimetric, prolongation of term and quality of buildings operation, improvement of architectural decisions, etc.). The level of a design of external walls efficiency of multi‐storey residential buildings depends on very many factors, including: cost of the construction work, used materials and building mechanisms, aesthetics, properties of service, thermal insulation properties, durability, etc. The offered decision of the choice of the effective decision problem using the system of the criteria having different dimensions takes into account the rational estimation of economic, climatic, social conditions and traditions and also allows better to satisfy architectural, functional, service, comfort and other requirements of the client. It also allows to reduce design, building and operational expenses. The choice of a variant mainly depends on needs and existing financial ability of the customer. The offered system of the effective decision choice using the principles of the multi‐criteria analysis is described in the presented paper. There is an opportunity on the basis of the offered system to compare alternative design decisions of external walls of multi‐storey residential buildings and the choice of the most effective variants. Article in Lithuanian. Daugiabučių gyvenamųjų namų išorės sienų sprendinių efektyvumo vertinimas daugiakriterinės analizės metodais Santrauka. Daugiabučių gyvenamųjų namų racionalumas labai priklauso nuo išorinių sienų konstrukcijų efektyvumo. Šiuolaikiniai tokių namų užsakovai ‐ investuotojai dažniausiai projektą įgyvendina efektyviai, bet kartais vadovaujasi vieninteliu kriterijumi – pelnu. Siūloma išorės sienų konstrukcijoms parinkti taikyti daugiakriterinės analizės metodus. Taip būtų galima užtikrinti išorinių sienų konstrukcijų efektyvumą viso pastato gyvavimo proceso metu, pradedant nuo poreikių bei tikslų nustatymo stadijos iki pastato naudojimo pabaigos. Nagrinėtuose išorės sienų trijų sluoksnių mūro konstrukciniuose sprendimuose panaudotos populiariausios šiuo metu Lietuvoje medžiagos. Uždaviniui spręsti sudaryta 7 efektyvumo kriterijų sistema, nustatytas tų kriterijų reikšmingumas. Reikšminiai žodžiai: sienos, sprendimu priėmimas, kriterijai, daugiakrterinė analizė, lošimų teorija, įvertinimas, efektyvūs variantai. First Published Online: 21 Oct 2010